Profitability of energy sector companies of Saudi Arabia: Mutual analysis based on revenue and investment - Ali, Anis; Alam, Mohammad Zulfeequar (Accounting, 2021)
The profitability of the business organization is the relative measurement and explores the profit earning capacity. There are two concepts of measuring profitability, which are profitability based on revenue, and investments. Gross and net profitability are the means of expression of the profitability based on revenue while investment profitability can be measured based on owners’ investment and total investment or total assets. Secondary data from the websites of the energy sector companies are taken for the study and ratio analysis, rank correlation is applied to get the similarity or differences in the profitability and relational relationship of the energy sector companies of Saudi Arabia. The study reveals that there was a significant difference in the profitability of the energy sector companies. Possibly, internal and external factors of the business organizations govern the profitability. There is a perfect and positive relational correlation between revenue and profitability while a highly negative correlation exists between profitability and investments. This may be due to overcapitalization or underutilization of the resources. Enhancement of velocity of operational activity is necessary to enhance the operational level of energy sector companies of Saudi Arabia. There is a need to control the indirect manufacturing and administrative expenses in smaller organizations and further investment in the energy sector companies is not advisable.